Floridians’ Perceptions of Endangered Species - Mary Hannah Miller; Nicole M. W. Dodds; Alexa J. Lamm (EDIS, 2014)
In July 2014, the UF/IFAS Center for Public Issues Education in Agriculture and Natural Resources (PIE Center) initiated a study to explore the attitudes, perceptions, opinions, and knowledge of Floridians on endangered and invasive species. The majority of respondents to the survey have favorable views of endangered species but few consider themselves knowledgeable on the issue. This 4-page fact sheet can equip Extension faculty to more effectively communicate with and educate clientele about endangered species. Written by Mary Hannah Miller, Nicole M.W. Dodds, and Alexa J. Lamm, and published by the UF Department of Agricultural Education and Communication, October 2014.